2018
DOI: 10.5334/joc.4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Context Influences the Perceived Duration of Everyday Actions: Assessing the Ecological Validity of Lab-Based Timing Phenomena

Abstract: Timing is key to accurate performance, for example when learning a new complex sequence by mimicry. However, most timing research utilizes artificial tasks and simple stimuli with clearly marked onset and offset cues. Here we address the question whether existing interval timing findings generalize to real-world timing tasks. In this study, animated video clips of a person performing different everyday actions were presented and participants had to reproduce the main action's duration. Although reproduced dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Similar reasoning also holds when considering the parameterization of the task used to measure the context effects. For example, in the work reported in this study, we remained close to our earlier studies in which we asked participants to end a machine-initiated interval by a single keypress (e.g., Schlichting et al, 2018;Van Rijn & Taatgen, 2008). However, it has been demonstrated that the method used for reproducing durations influenced both accuracy and precision, with an offset-keypress associated with lower precision than having the participant keep a key depressed for the duration of the reproduction (Mioni, Stablum, McClintock, & Grondin, 2014, see also Damsma, Schlichting, & Rijn, 2019).…”
Section: Bottom-up Influencesmentioning
confidence: 75%
“…Similar reasoning also holds when considering the parameterization of the task used to measure the context effects. For example, in the work reported in this study, we remained close to our earlier studies in which we asked participants to end a machine-initiated interval by a single keypress (e.g., Schlichting et al, 2018;Van Rijn & Taatgen, 2008). However, it has been demonstrated that the method used for reproducing durations influenced both accuracy and precision, with an offset-keypress associated with lower precision than having the participant keep a key depressed for the duration of the reproduction (Mioni, Stablum, McClintock, & Grondin, 2014, see also Damsma, Schlichting, & Rijn, 2019).…”
Section: Bottom-up Influencesmentioning
confidence: 75%
“…Whereas participants might be influenced by recent objective durations, it is also possible that they rely on their subjective experience of this objective duration, i.e., their own temporal production (e.g., Schlichting et al, 2018). To test this idea, we again started with the previously established model mentioned in Section 3.4.1, and sequentially added previous subjective durations (in trial N-1, N-2, N-3, etc.…”
Section: Subjective Previous Durationsmentioning
confidence: 99%
“…For example, in certain phases of the experiment, a participant might be less willing to make longer responses compared to other phases. To disentangle the influence of the previous subjective duration from this local performance drift, we calculated the relative error of the reproduction in each trial (error = [reproduced duration -objective duration]/objective duration) (see Schlichting et al, 2018). In the case of performance drift, we would expect that a negative error (that is, a too short reproduction) in the previous trial would also lead to negative error in the current trial.…”
Section: Subjective Previous Durationsmentioning
confidence: 99%
“…Although there is abundant behavioral evidence for Bayesian integration in human time perception (Acerbi, Wolpert, & Vijayakumar, 2012;Cicchini, Arrighi, Cecchetti, Giusti, & Burr, 2012;Gu, Jurkowski, Lake, Malapani, & Meck, 2015;Hallez, Damsma, Rhodes, van Rijn, & Droit-Volet, 2019;Jazayeri & Shadlen, 2010;Maaß, Riemer, Wolbers, & van Rijn, 2019;Maaß, Schlichting, & van Rijn, 2019;Roach, McGraw, Whitaker, & Heron, 2017;Schlichting et al, 2018;Shi, Church, & Meck, 2013), its temporal locus and neural underpinnings are not yet understood.…”
Section: Introductionmentioning
confidence: 99%